2019
DOI: 10.1039/c9sc03374b
|View full text |Cite
|
Sign up to set email alerts
|

Two 3′-O-β-glucosylated nucleoside fluorometabolites related to nucleocidin in Streptomyces calvus

Abstract: Two novel 3′-O-β-glucosylated nucleosides are identified from Streptomyces calvus fermentations prior to nucleocidin production, suggesting an early role during the biosynthesis of this antibiotic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
70
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(75 citation statements)
references
References 24 publications
2
70
0
Order By: Relevance
“…Upon complementation with a functional gene, S. calvus produced nucleocidin once again, which was detected by 19 F NMR. Subsequent biosynthetic investigations, again relying on 19 F NMR, have revealed that the elaboration of this unusual fluorometabolite involves the production of glucosylated precursors [119], which are detectable in the culture supernatant (Figure 18). These are possibly inactive forms of nucleocidin, generated in the first instance so that the producing organism is protected from its deleterious effects, and can be activated outside the cell by glucosidases.…”
Section: Detection and Biosynthesis Of Natural Organofluorine Compoundsmentioning
confidence: 99%
“…Upon complementation with a functional gene, S. calvus produced nucleocidin once again, which was detected by 19 F NMR. Subsequent biosynthetic investigations, again relying on 19 F NMR, have revealed that the elaboration of this unusual fluorometabolite involves the production of glucosylated precursors [119], which are detectable in the culture supernatant (Figure 18). These are possibly inactive forms of nucleocidin, generated in the first instance so that the producing organism is protected from its deleterious effects, and can be activated outside the cell by glucosidases.…”
Section: Detection and Biosynthesis Of Natural Organofluorine Compoundsmentioning
confidence: 99%
“…[32] Intriguingly enough, despite of the variety of effects and molecular targets they exhibit, naturally occurring halogenated metabolites are largely restricted to secondary microbial metabolism and they are essentially absent in macromolecules. Natural halogenated polysaccharides have not been reported and, in general, halogenated carbohydrates are rare, [33] although a few have been identified, for example, two 4'-fluoro-3'-O-βglucosylated metabolites isolated from Streptomyces calvus [34] and a chloro-glycosylated antitumoral molecule synthesized by Pseudomonas sp. strain 2663.…”
Section: Natural and Synthetic Occurrence Of Organohalidesmentioning
confidence: 99%
“…In 2019, O'Hagan group disclosed two structures of novel fuorometabolites in S. calvus, which belong to 3′-O-glucosylated, 4′-fuoro-riboadenosines (6 and 7) (Scheme 1a). They are analogous of nucleocidin 1 and suspect to incorporate fluorine via a same biocatalytic pathway (Feng et al 2019). The identification of these metabolites highly suggests that there is a new type of fluorinase existing in S. calvus which deserves our attention.…”
Section: Enzyme-catalyzed C-f Bond Formationmentioning
confidence: 99%